Job Scheduling Strategies for Parallel Processing 16th International Workshop, JSSPP 2012, Shanghai, China, May 25, 2012. Revised Selected Papers - Cirne, Walfredo; Desai, Narayan; Frachtenberg, Eitan; Schwiegelshohn, Uwe.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed proceedings of the 16th International Workshop on Job Scheduling Strategies for Parallel Processing, JSSPP 2012, which was held in Shanghai, China, in May 2012. The 14 revised papers presented were carefully reviewed and selected from 24 submissions. The papers cover the following topics: parallel batch scheduling; workload analysis and modeling; resource management system software studies; and Web scheduling.
Parallel batch scheduling -- Workload analysis and modeling -- Resource management system software studies -- Web scheduling.
Keywords: Computer science; Computer Communication Networks; Software engineering; Operating systems (Computers).; Computer software; Computer simulation; Computer Science; Software Engineering; Operating Systems; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Software Engineering/Programming and Operating Systems; Simulation and Modeling